Analisis Kemampuan Literasi Digital Guru dalam Penggunaan Literasi Informasi dan Literasi Media Pembelajaran Berbasis Teknologi di SD Negeri Pandan Sari Kecamatan Manyak Payed Kabupaten Aceh Tamiang - Nurida Nurida; Nadila Aldyza; M Danil (Jurnal Ilmiah Global Education, 2026)
This study analyzes elementary school teachers' digital literacy skills, specifically information and media literacy, in technology-based learning at SD Negeri Pandan Sari. Using qualitative descriptive methods with interviews, observations, and documentation analyzed through NVivo 15, the research reveals that teachers possess strong information literacy skills with ethical foundations and critical thinking, successfully converting information into engaging visual media. They demonstrate adequate media literacy, serving as creators of meaningful learning experiences and instructional designers. Key influencing factors include internal aspects (adaptive mindset, varied competencies, motivation, and confidence) and external factors (collaborative culture, budget availability, curriculum dynamics, infrastructure, and parental support). Despite 21st-century learning demands and challenges like limited training and digital access, teachers show continuous improvement in developing effective, varied teaching materials.